2019
DOI: 10.3390/molecules24020258
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Nine Mentha Species and Prediction of Their Antioxidant Properties Using Chemometrics

Abstract: Mentha species are well recognized for their medicinal and aromatic properties. The comprehensive metabolite profiles of nine Mentha species have been determined. The extracts of these Mentha species were also screened for antioxidant and free radical scavenging activities. Forty-seven hydrophilic and seventeen lipophilic compounds were identified and quantified from the selected Mentha species. Also, eleven phenolic compounds, riboflavin and eight carotenoids were present, and their composition and content va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 29 publications
(36 reference statements)
1
29
0
1
Order By: Relevance
“…This would be a response to the high content of these Compounds in these drying methods. The polyphenols present in spices have positive effects on health, proving the effectiveness by in vitro tests of the elimination of free radicals (DPPH and ABTS) and the reduction of metal ions (FRAP) [30], in such a way that this could be an explanation of the antioxidant activities of spices. The biological activity of plants is shown to be useful for the treatment of various diseases, especially chronic non transmissible diseases such as diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…This would be a response to the high content of these Compounds in these drying methods. The polyphenols present in spices have positive effects on health, proving the effectiveness by in vitro tests of the elimination of free radicals (DPPH and ABTS) and the reduction of metal ions (FRAP) [30], in such a way that this could be an explanation of the antioxidant activities of spices. The biological activity of plants is shown to be useful for the treatment of various diseases, especially chronic non transmissible diseases such as diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…Rutin content was found to be in significant correlation with the FRAP activity of M. longifolia (Patonay et al 2017). Park et al (2019) also observed strong antioxidant activity to their rutin-dominated M. longifolia sample. Further studies are suggested to determine if higher concentrations of quercetin derivatives are really universal characteristics to this species as it was described in some references above.…”
Section: Discussionmentioning
confidence: 79%
“…(20,000-80,000 mg/kg dp). On the other hand, a recent work (Park et al 2019) gives unconventionally low RA concentration (18.68 lg/g dp. viz.…”
Section: Rosmarinic Acidmentioning
confidence: 89%
See 2 more Smart Citations